Legal Study On Foreign Ownership In The Oil Palm Plantation Sector From The Perspective Of Indonesia’s Economic Sovereignty - Situmorang, Patricia Catheleene Joty; Sukarja, Detania; Robert, Robert (Ultimate Journal of Legal Studies, 2024)
Palm oil plantations are a leading Indonesian commodity with a strategic role. Foreign investment activities are subject to Law No. 25 of 2007 concerning Investment and Presidential Regulation No. 10 of 2021, which was later amended by Presidential Regulation No. 49 of 2021. Under these regulations, palm oil plantations do not require restrictions on capital ownership, meaning they can be fully owned by foreigners. This research addresses the legal aspects of foreign investment in the palm oil plantation sector, examines whether the size of foreign ownership correlates with the challenges posed by palm oil plantations, and examines whether existing regulations regarding Foreign Direct Investment (FDI), particularly in the palm oil plantation sector, are effective in ensuring economic sovereignty. Using normative legal research methods. The results indicate that the environmental and social impacts of palm oil plantations are not directly correlated with the company's ownership structure but rather relate to the company's operational practices and approach to local communities. Furthermore, although the state does not limit the size of foreign capital ownership, its presence in maintaining economic sovereignty is manifested in policies related to restrictions and obligations, such as those related to land rights, where investors can only hold a Cultivation Use Rights (HGU) for a specific period, and obligations regarding plasma plantation development and land allocation. This research also shows that regulations in oil palm plantations still require improvement to address overlapping and disharmonious regulations.